IDIOMS WITH NAMES OF FRUIT AND VEGETABLES IN ALBANIAN AND IN GREEK - Miconi, Harallamb; Rapi, Leonard; Kote, Zamira (European Scientific Journal, ESJ, 2014)
The aim of this article is to study the idioms of the lexical field with names of fruit and vegetables and to see whether there are or there are not idiomatic parallels between the Albanian idioms and the Greek ones. The starting point for this study is the inclusion of these words in idioms, i.e., their cultural connotation in both languages as well as the cultural and geographical closeness between the peoples who speak these languages. The main conclusion drawn from this study is that there are not idiomatic parallels between the two languages, but original idiomatic developments the understanding of which depends on the understanding of everyday life, natural conditions and social norms. Semantic non-correspondence between them poses difficulties in the translation of these expressions in the respective languages. These difficulties increase even more when the expressions have the same lexical composition, which leads to semantic false friends, such as janë bathët të numëruara (Alb.) (counted beans, lit.) for someone’s limited economic abilities and μετρημένα κουκιά (Gr.) (counted beans, lit.) for accurate calculation of things in a given situation.